Management Information Systems in Production and Education - Pozeichuk, Andrii; Hrama, Mykhailo (My University, 2025)
Modern society is at the stage of digital transformation, which covers all spheres of human activity - from industry to education. One of the key areas of this transformation is the implementation of information management systems (ISMs), which allow to increase the efficiency of process management, automate routine operations and improve the quality of managerial decision-making. Information systems are becoming the basis not only for production management, but also for educational institutions that adapt to the new requirements of the digital economy. Сучасне суспільство перебуває на етапі цифрової трансформації, яка охоплює всі сфери людської діяльності – від промисловості до освіти. Одним із ключових напрямків цієї трансформації є впровадження систем управління інформацією (СІУ), які дозволяють підвищити ефективність управління процесами, автоматизувати рутинні операції та покращити якість прийняття управлінських рішень. Інформаційні системи стають основою не лише для управління виробництвом, а й для навчальних закладів, що адаптуються до нових вимог цифрової економіки.
Keywords: machine learning; big data; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; машинне навчання; великі дані